PERCEPTIONS OF FILIPINO TEACHERS TOWARD ONLINE TEACHING - Macrohon, Angle Claire; Dalagam, Anjalie Grace; Escares, Christine Joy; Mallati, Faizalyn; Edding, Ibtisam; Ubarra, Sherwina; Quililan, Crizy Jane; Handang, Juspher; Sajirun, Aljumar; Lemana, Jewel Doreen; Gregorio, Kathleen; Villahermosa, Julie mae (Journal of Education and Innovation, 2023)
The central problem investigated in this study is to determine the perceptions of teachers toward online teaching. In doing this, the study has accumulated data from Western Mindanao State University, Zamboanga City This study was purely a qualitative method of research, specifically a phenomenological design to examine the substance of human experiences concerning a phenomenon. Through the non-probability sampling, particularly the convenience sampling, made the in-depth one-on-one interview possible and we were able to accumulate the data needed for answering the research questions. Results showed, out of the five (5) responses of the teacher-respondents, they viewed online teaching as helpful in times of pandemic, for instance in delivering the lesson and continuing to interact with the students virtually. In addition, respondents viewed online teaching as not a hindrance to students’ achievement. Though classes are more online-focused, students can still develop their literacy skills. There were also identified problems in online teaching, such as unstable internet connections, electric power interruptions, assessing students, gadgets, and platforms used. However, as the teacher-respondents pointed out, these cannot be a barrier because they all have plans in place before this could occur. The teacher-respondents from Integrated Laboratory School under the supervision of Western Mindanao State University in the Philippines have positive perceptions toward online teaching as one of the alternative ways to continue the quality of education being delivered to students. Despite problems encountered while teaching, they manage to search for possible courses of action; additionally, with a true passion for teaching, being adaptive, versatile, and flexible, these problems cannot be a hindrance.